Environmentally conscious mechanical design - Kutz, Myer (Wiley series in environmentally conscious engineering, 2007)
This volume focuses on environmental design - understanding it and implementing it. Coverage includes the important technical and analytical techniques and best practices of designing industrial, business, and consumer products that are environmentally friendly and meet environmental regulations.